Absent Secretion to Vasoactive Intestinal Peptide in Cystic Fibrosis Airway Glands - Joo, Nam Soo; Irokawa, Toshiya; Wu, Jin V.; Robbins, Robert C.; Whyte, Richard I.; Wine, Jeffrey J. (The Journal of biological chemistry, 2002)
We are testing the hypothesis that the malfunctioning of airway gland serous cells is a component of cystic fibrosis (CF) airway disease. CF is caused by mutations that disrupt CF transmembrane conductance regulator, an anion channel essential for proper fluid secretion in some epithelia. Submucosal glands supply most of the mucus in upper airways, and gland serous cells are the primary site of CF transmembrane conductance regulator expression in airways. We have discovered a major defect in CF glands by in situ optical monitoring of secretions from single human airway glands. CF glands did not secrete to agents that elevated [cAMP]i (0 responses/450 glands, 8 subjects), whereas glands were responsive in all donor tracheas (605/827 glands, 15 subjects) and in bronchi from subjects who were transplanted because of other lung diseases (148/166 glands, n = 10). CF glands secreted to cholinergic stimulation, and serous cells were abundant in glands from all CF subjects. The complete absence of secretion to agents that elevate [cAMP]i suggests that altered secretion of gland mucus could contribute to CF lung disease.